Analisis Kemampuan Guru dalam Menggunakan KIT IPA di Kelas Tinggi SD Negeri Jurong Mesjid Kabupaten Pidie - Falyatun Husna; Suci Fitriani; Sulaiman Sulaiman (Universitas Syiah Kuala, 2022)
The purpose of this study was to analyze the teacher's ability to use KIT IPA in the high class of SD Negeri Jurong Mesjid, Pidie. In particular, this study aims to describe the teacher's ability to use KIT Science in the High Class of Jurong Mesjid Elementary School, Pidie Regency. The approach in this study is a qualitative approach with a descriptive type of research. The subjects of this study were high grade teachers, namely grades IV, V, VI at Jurong Mesjid Elementary School, Pidie Regency. Data was collected by using interview and observation techniques. Interview and observation techniques were carried out with high grade teachers at Jurong Mesjid State Elementary School. The results of the research in class V can be concluded that, in class V on simple planes the teacher uses the KIT IPA pulley as a tool for experiments, the teacher uses pulleys to conduct experiments on types of simple machines. The teacher selects sub-chapters according to the material being taught, the teacher also uses the KIT science according to the instructions/steps for using the KIT, the teacher also conducts an experimental process using the right KIT science according to the expected competencies. While class VI the teacher uses the KIT IPA magnet as a tool for experiments, in this experiment the teacher explains first about magnets and their uses, before conducting the experiment the teacher first gives examples to students about objects that can be attracted and cannot be attracted by magnets, The teacher also involves students in conducting experiments, so as to make students understand more about the material